Vitamin D Regulates Cytokine Patterns Secreted by Dendritic Cells to Promote Differentiation of IL-22-Producing T Cells - Sommer, Andrea; Fabri, Mario (PLOS ONE, 2015)
One central mechanism, by which vitamin D regulates human immune responses, is the direct modulation of dendritic cells (DCs). However, the effect of vitamin D on several key DC functions, such as the secretion of central inflammatory cytokines, remains controversial. Moreover, whether vitamin D treatment of DCs regulates their ability to promote differentiation of IL-17-/IL-22-producing T cell subsets, such as Th17 and Th22 cell, is not known. Here, we report that vitamin D treatment during differentiation of monocytes into DCs markedly enhanced their ability to secrete TNF-α, IL-6, IL-1β and IL-23. Cytokines secreted by vitamin D-treated DC were significantly more potent in driving differentiation of IL-22-producing T cells, but not IL-17-producing T cells, as compared to secreted cytokines of not-vitamin D-treated DCs. Finally, we found that the differentiation of IL-22-producing T cells mediated by supernatants of vitamin D-treated DCs was dependent on TNF-α IL-6 and IL-23. In summary, our study suggests a novel role of vitamin D in regulating DC-mediated immune responses in humans.